Race and Prejudice: Constructing Identity in “The Help” Movie - Afifulloh, Muhammad; Saputra, Arfian Dwi; Theresa, Gracia Petra; Kurnia, Happy; Setyawan, Tedi; Dwitama, Wahyu Rismayuda (English Education Department, 2024)
This study aimed to describe and analyze the representation of racism in the film